Descriptive adequacy of early modern English grammars - Dons, Ute, 1971- (Topics in English linguistics, 2004)
The book deals with the development of descriptive models of English grammar writing during the Early Modern English period. For the first time, morphology and syntax as presented in Early Modern English grammars are systematically investigated as a whole. The statements of the contemporary grammarians are compared to hypotheses made in modern descriptions of Early Modern English and, where necessary, checked against the Early Modern English part of the Helsinki Corpus. Thus, a comprehensive overview of the characteristic features of Early Modern English is complemented by conclusions about the descriptive adequacy of Early Modern English grammars. It becomes evident that comments by contemporary authors occasionally reflect the corpus data more adequately than the statements found in modern secondary literature. This book is useful for (advanced) university students, as well as for scholars of English and grammarians in general.